Immunization With a Live-Attenuated RH:ΔNPT1 Strain of Toxoplasma gondii Induces Strong Protective Immunity Against Toxoplasmosis in Mice - Yang, Wen-Bin; Wang, Jin-Lei; Gui, Qian; Zou, Yang; Chen, Kai; Liu, Qing; Liang, Qin-Li; Zhu, Xing-Quan; Zhou, Dong-Hui (Frontiers in Microbiology, 2019)
Toxoplasmosis, one of the most important health-threatening diseases worldwide, is caused by Toxoplasma gondii, which infects a wide range of warm-blooded animals and humans, leading to enormous health and socioeconomic concerns. T. gondii can establish chronic infection to evade the immune response in hosts. Once a chronic infection has been established, the available treatments cannot efficiently control this stage of T. gondii efficiently. Moreover, the available treatments rely only on a few drugs, such as sulfapyridine and pyrimethamine, that tend to have severe side effects. Given these factors, vaccination has been considered to be the most efficient method to prevent and control this disease. However, there is currently lack of effective vaccine available for use to prevent toxoplasmosis apart form Toxovax®, the only available vaccine, which is used in sheep to prevent abortion. To address this problem, we knocked out the NPT1 gene of the type I T. gondii strain using the CRISPR-Cas9 system, constructed a live-attenuated vaccine and evaluated its protective efficacy in a mouse model. Immunization of mice with RH:ΔNPT1 induced a high level of Toxoplasma-specific IgG1, IgG2a and total IgG 42 days after immunization. There was a significant increase in the levels of cytokines in the splenocyte suspensions of RH:ΔNPT1-infected mice, and a mixed Th1/Th2 response was induced in the mice. Remarkably, after heterologous challenges with tachyzoites of the RH, PYS and Pru strains and cysts of the Pru strain by different infection routes, the immunized animals were protected from toxoplasmosis with a 100% survival rate, in both acute and chronic infection. In addition, compared with control mice, the Pru cyst load was clearly reduced in the brains of RH:ΔNPT1-infected immunization-mice. Our study demonstrated that the RH:ΔNPT1 strain was able to evoke strong anti-Toxoplasma immune responses and provide effective protection against parasite strains with different levels of virulence, suggesting that the RH:ΔNPT1 strain may represent a promising live-attenuated vaccine against toxoplasmosis, which is worthy of further evaluation in food-producing animals and in definitive feline host.